Gene Model Annotations for Drosophila melanogaster: The Rule-Benders. Issue 8 (1st August 2015) - Crosby, Madeline A; Gramates, L Sian; dos Santos, Gilberto; Matthews, Beverley B; St. Pierre, Susan E; Zhou, Pinglei; Schroeder, Andrew J; Falls, Kathleen; Emmert, David B; Russo, Susan M; Gelbart, William M; ,
Abstract: In the context of the FlyBase annotated gene models in Drosophila melanogaster, we describe the many exceptional cases we have curated from the literature or identified in the course of FlyBase analysis. These range from atypical but common examples such as dicistronic and polycistronic transcripts, noncanonical splices, trans -spliced transcripts, noncanonical translation starts, and stop-codon readthroughs, to single exceptional cases such as ribosomal frameshifting and HAC1-type intron processing. In FlyBase, exceptional genes and transcripts are flagged with Sequence Ontology terms and/or standardized comments. Because some of the rule-benders create problems for handlers of high-throughput data, we discuss plans for flagging these cases in bulk data downloads.